Análisis visual de una imagen escrita: estudio contemporáneo de la hypotiposis - González Calvo, Sofía (Escritura e Imagen, 2007)
Through the figure of hypotiposis, the work attempts to identify the specific qualities that enable a text to give the impression of becoming an image. For this purpose, instruments developed in the field of visual studies are applied: Wölfflin’s dualities, Gombrich and Arnheim’s writings, gestalt, the Theory of perception, etc. As a first exercise, a text by illustrator and novelist Mervyn Peake was selected and analysed in terms of its visual and narrative effectiveness as if it were a painting, the aim being to demonstrate that within certain texts with a high degree of visual richness, images configure a supertext of non-explicit connotations that are superimposed on the verbal.